2003
DOI: 10.1023/b:caco.0000003841.54413.98
|View full text |Cite
|
Sign up to set email alerts
|

Diet and premalignant lesions of the cervix: evidence of a protective role for folate, riboflavin, thiamin, and vitamin B12

Abstract: Objective: A case-control study was conducted among a population of multiethnic women identified from clinics on Oahu, Hawaii between 1992 and 1996 to explore the relationship between diet and cervical dysplasia. Methods: Two-hundred and fourteen women with biopsy-confirmed high and low grade squamous intraepithelial lesions of the cervix (SIL) and 271 controls were identified. Exfoliated cervical cells were collected for HPV DNA testing. Surveys were administered to assess non-dietary risk factors and intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 40 publications
2
42
0
7
Order By: Relevance
“…Data on the association between nutritional factors and cervical neoplasia risk are sparse and inconsistent (Liu et al, 1993;Goodman et al, 2000Goodman et al, , 2007Yeo et al, 2000;Shannon et al, 2002;Hernandez et al, 2003;Garcia-Closas et al, 2005;Goodman et al, 2007;World Cancer Research Fund/American Institute for Cancer Research, 2007;Ghosh et al, 2008). Liu et al (1993) found no association between calcium intake and cervical dysplasia, with a multivariate-adjusted OR for the highest to lowest level of intake of 0.9 (95% CI 0.4-2.1; trend P ¼ 0.58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the association between nutritional factors and cervical neoplasia risk are sparse and inconsistent (Liu et al, 1993;Goodman et al, 2000Goodman et al, , 2007Yeo et al, 2000;Shannon et al, 2002;Hernandez et al, 2003;Garcia-Closas et al, 2005;Goodman et al, 2007;World Cancer Research Fund/American Institute for Cancer Research, 2007;Ghosh et al, 2008). Liu et al (1993) found no association between calcium intake and cervical dysplasia, with a multivariate-adjusted OR for the highest to lowest level of intake of 0.9 (95% CI 0.4-2.1; trend P ¼ 0.58).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the majority of women with HPV infection do not develop cervical cancer, and the involvement of other etiological factors, such as smoking, oral contraceptive use, gravidity or diet, has thus been suggested (Verreault et al, 1989;Nagata et al, 1999;Kjellberg et al, 2000;Yeo et al, 2000;Shannon et al, 2002;Hernandez et al, 2003;Shields et al, 2004;Garcia-Closas et al, 2005; World Cancer Research Fund/American Institute for Cancer Research, 2007). With regard to diet, however, data are presently too sparse to allow the drawing of any conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Human population studies show that a high dietary folate intake is associated with a diminished risk of colorectal cancer [1][2][3] and, possibly, of cancers of the breast [4][5][6], uterine cervix [7][8][9], lung [10,11], esophagus and pancreas [12] as well. The inverse association between folate status and the risk for carcinogenesis is thought to be explained by the role of folate coenzymes in providing one-carbon moieties for nucleotide and S-adenosylmethionine (via methionine) synthesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiologic studies have reported a relationship between cervical cancer and diets low in riboflavin (Hernandez et al, 2003), and animal studies have shown that riboflavin deficiency can lead to disruption of the esophagus epithelium, in a similar manner to precancerous Jun-Qi Ma 1 , Shajidai Kurban 2 , Jun-Da Zhao 1 , Qiao-Zhi Li 2 *, Ayshamgul Hasimu 2 lesions in human's cervical cancer (Murphy et al, 2010). Riboflavin also participates in various metabolic redox reactions, and is involved in one carbon metabolism, which is a network of interrelated biochemical pathways that generate one carbon groups needed for physiologic processes (De Souza et al, 2006).…”
Section: Introductionmentioning
confidence: 99%